Recent progress in ceria-based catalysts for the dry reforming of methane: A review - L. P., Teh; Setiabudi, H. D.; S. N., Timmiati; M. A. A., Aziz; N. H. R., Annuar; N. N., Ruslan (Elsevier, 2021)
The mitigation of CO2 and CH4 emissions is feasible by transforming them into valuable syngas via the dry reforming of methane (DRM). However, the problem of catalyst deactivation has restricted its industrial application. Therefore, the development of catalysts for an effective reforming process has been attracted enormous attention. Ceria has a high potential as it can serve as both catalyst support and metal active site for adsorption and dissociation of CO2 and CH4. Material properties, such as redox and acid/base properties, and oxygen storage capacity, greatly affect catalytic behavior and performance, as well as coke inhibition in the DRM. This review aims to provide an up-to-date summary on the DRM over ceria-based catalysts, including aspects of the catalysts, reaction mechanism, deactivation, and regeneration studies. This review also proposes governing factors and new ways for improving the process, to provide a more rational to designing an ideal ceria-based catalyst for DRM.